Konsep Being Perspektif Filsafat dan Islam - Suhermanto Jakfar (Islamica: Jurnal Studi Keislaman, 2017)
This article discuss the concept of being in the perspective of existentialism and Islam. The closest similarity to the word â€œbeingâ€ is to on (Ancient Greece), as the word of einai, to be (on, onta). For Parmenides, â€œbeingâ€ (to on) is one, eternal and unchanging. Gabriel Marcel calls the way the human being with the term Ãªtre-au-monde, etre in carne, geist-in-welt. Martin Heidegger uses a formula being in the world to characterize human life. Being in the world as a feature of human life, human beings are in the situation. Living in a world of concrete means that there are human relationships with the situation. Sartre said that the real one where there are two, namely: Iâ€™etre en soi and Iâ€™etre pour Soi. For Sartre, Iâ€™etre en soi is the idea that only a concrete phenomenon has ontological status; only something concrete is real. Unlike the being-in-itself, for Sartre the concept of being-for-itself is a state of being that comes with the awareness and self-control. The concept of being (wujÃ»d) by SuhrawardÃ® is a mental concepts (mahfÃ»m) that do not have the type and diferensia. In the illumination philosophy of SuhrawardÃ®, the idea of â€‹â€‹wujÃ»d can not be separated from nature and depiction of light. The philosophy of wujÃ»d by Mulla SadrÃ¢ stands on three basic principles of fundamental importance. These three principles are as follows: wahdat al-wujÃ»d, tashkÃ®k al-wujÃ»d, and tashkÃ®k. While Mohammad Iqbal emphasis on metaphysics and anthropological philosophy. Iqbal gives greater emphasis on more concrete dimensions, namely khudi (ego).